(untitled) (Journal of Oriental Studies, 2016)
this article discusses the place of sufism in india and its impact, which concerned the mystical life of india. the main attention is drawn to the orders, and sufi. sufi theme continues the historical period in the literature, which is the spiritual basis of the trend values. because the issue is much needed research topics sufi literature. since sufism during the worldview that recognizes india, the article focuses on its place in the worldview, the historical situation, the spiritual life of the hindus, reflected in the works of sufi who lived in the middle ages.